2022
DOI: 10.1111/bph.15726
|View full text |Cite
|
Sign up to set email alerts
|

20‐hydroxyeicosatetraenoic acid (20‐HETE) is a pivotal endogenous ligand for TRPV1‐mediated neurogenic inflammation in the skin

Abstract: Background and Purpose: Transient receptor potential cation channel subfamily V member 1 (TRPV1) is localized to sensory C-fibres and its opening leads to membrane depolarization, resulting in neuropeptide release and neurogenic inflammation. However, the identity of the endogenous activator of TRPV1 in this setting is unknown.The arachidonic acid metabolites 12-hydroperoxyeicosatetraenoyl acid (12-HpETE) and 20-hydroxyeicosatetraenoic acid (20-HETE) have emerged as potential endogenous activators of TRPV1. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Among the identified compounds, arachidonic acid metabolites were especially promising candidates as these compounds are components of glycerophospholipids with broad bioavailability and had been previously implicated in inflammation as well as pain and itch processes. One metabolite, 20-hydroxyeicosatetraenoic acid (20-HETE), had previously been reported to activate TRPV1 25 . Based on these reasons, we further quantified 20-HETE availability in the skin by UHPLC (Figure 7 D-F).…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified compounds, arachidonic acid metabolites were especially promising candidates as these compounds are components of glycerophospholipids with broad bioavailability and had been previously implicated in inflammation as well as pain and itch processes. One metabolite, 20-hydroxyeicosatetraenoic acid (20-HETE), had previously been reported to activate TRPV1 25 . Based on these reasons, we further quantified 20-HETE availability in the skin by UHPLC (Figure 7 D-F).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 20-HETE is one of the arachidonic acid (AA) metabolites, being the endogenous ligand for transient receptor potential cation channel subfamily V member 1 (TRPV1). By activating TRPV1, 20-HETE could aggravate neurogenic inflammation and ischemic neuronal injury ( Zhang et al., 2018 ; Hamers et al., 2021 ). Moreover, TRPV1 is functionally expressed in rat vestibular ganglia ( Kamakura et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…For serum analysis, one study reported that AA-derived mediators LTB4, TXB2, hydroxy-octadecadienoic acids (HODEs), and hydroxy-eicosatetraenoic acids (HETEs) were significantly higher in the AD group compared to the non-AD group in children [115,116]. These mediators act as chemoattractants for leukocyte recruitment and may be involved in the itch response [117][118][119]. Sphingosine-1-phosphate (S1P) was also elevated in AD patients and was shown to correlate with disease severity [120].…”
Section: Atopic Dermatitismentioning
confidence: 99%